2022
DOI: 10.1088/1361-6463/ac4454
|View full text |Cite
|
Sign up to set email alerts
|

Metal-wire-embedded alumina insulating material using micro- and nanoscale 3D printing for surface flashover mitigation in a vacuum

Abstract: Micro and nanoscale 3D printing technic is applied to fabricate functional insulating material which mitigates surface discharge in vacuum based on the microscopic electron multipactor suppression. The proposed alumina ceramic insulator design consists surface-embedded thin metal wires which introduce a local gradient of secondary electron emission yield, such that the trajectories of multipactor electrons are distorted by accumulated negative surface charges and the secondary electron emission avalanche acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…By contrast, the δ max and corresponding A max of the CuO@PI/SrO@PI/MgO@PI/Al 2 O 3 @PI coated films are 1.59/1.58/1.71/2.02 and 400/300/200/300 eV, respectively. It has been demonstrated that the SEE plays a dominant role in determining the flashover discharge development process, and the reduction of SEY is usually favorable for flashover mitigation. ,, This is because lower SEY inhibits the formation of the SEEA and hence the subsequent desorbed gas breakdown. Analytical flashover theory suggests that the flashover voltage increases with lower SEY, with the voltage approximately proportional to the square root of the term A max δ max A 0 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the δ max and corresponding A max of the CuO@PI/SrO@PI/MgO@PI/Al 2 O 3 @PI coated films are 1.59/1.58/1.71/2.02 and 400/300/200/300 eV, respectively. It has been demonstrated that the SEE plays a dominant role in determining the flashover discharge development process, and the reduction of SEY is usually favorable for flashover mitigation. ,, This is because lower SEY inhibits the formation of the SEEA and hence the subsequent desorbed gas breakdown. Analytical flashover theory suggests that the flashover voltage increases with lower SEY, with the voltage approximately proportional to the square root of the term A max δ max A 0 1 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the SEE plays a dominant role in determining the flashover discharge development process, and the reduction of SEY is usually favorable for flashover mitigation. 22,63,64 This is because lower SEY inhibits . 21 Here A 0 is a known constant.…”
Section: Experimental Validation Of Trap Modulation and Flashover Mit...mentioning
confidence: 99%
“…Recently, Mu et al. [165] used a micro‐ and nanoscale 3D printing technique to embed metal wire on the insulator surface, the fabricated functional insulating material generates negative surface charges, and it causes surface flashover voltage increases by 35% when the width of metal wire is 0.4 mm.…”
Section: Competing Mechanisms Of Charge Transport In Surface Flashovermentioning
confidence: 99%
“…The occurrence of flashover mainly depends on the surface state of the dielectric, such as surface morphology, surface trap, surface charge migration, outgassing from surface, and accompanying gas ionization. Researchers have put forward various methods to modify the properties of the interface to improve the flashover voltage. Typical methods include introducing micro-nanostructures on the dielectric surface for morphology modification by 3D printing; modulating the interfacial charge migration behavior by cross-linking or fluorination; changing the surface traps by graphene, Cr 2 O 3 , and other nanoparticles; and regulating the outgassing rate and gas ionization by polythiourea-assisted coating. Although different modification strategies focus on modifying the interface properties from different perspectives, the ultimate goal is to improve the flashover voltage by suppressing surface charge accumulation and mitigate electric field distortion, which can suppress electron multiplication. , …”
Section: Introductionmentioning
confidence: 99%